Herstory as an Important Force in Bioethics. (26th April 2022) - Sodeke, Stephen; Fletcher, Faith E.; Brown, Virginia A.; Stone, John R.; Wilson, Cynthia B.; Franklin, Tené Hamilton; Royal, Charmaine D. M.; Bonham, Vence L.
Abstract: This tribute celebrates the life and work of Marian Gray Secundy (1938–2002), who was the first director of the National Center for Bioethics in Research and Health Care, a passionate advocate for health equity, a visionary scholar, and a skilled editor and collaborator. Within the tribute are several short remembrances in which individuals describe their association with Secundy to honor her as a leader, friend, scholar, advocate, and teacher in bioethics.